Design and construction of a new coaxial high voltage fast impulse current transducer - Abdul Malek, Zulkurnain (Faculty of Electrical Engineering, 2003)
Since the introduction of zinc-oxide material in 1968 much research has been directed towards the characterisation of the electrical behaviour of the material under various stress conditions. An aim of some of these investigations is to achieve an equivalent circuit representation, which adequately simulates the observed test results. An adequate equivalent circuit representation will aid the reliable and efficient design of the overvoltage protection and help to improve the optimisation of the protective devices. A significant impediment to the accurate characterisation of zinc oxide has been the lack of reliable test data especially for fast-rate-of-rise impulses in the microsecond and sub-microsecond range. The measurement of current impulses in this range is highly influenced by the circuit arrangement and measurement transducer characteristics. In this work, a non-inductive coaxial current shunt was designed and constructed. The fast impulse tubular current shunt was based on the nickel chromium resistive material with a designed value of 5mâ„¦ and 10kA current capability. The current shunt was successfully constructed except the nickel chromium material, which could not be successfully soldered to the aluminium casings. It is recommended that the work is to be completed in future projects.